2012
DOI: 10.1093/aobpla/pls004
|View full text |Cite
|
Sign up to set email alerts
|

Non-symbiotic haemoglobins—What's happening beyond nitric oxide scavenging?

Abstract: The ating evidence suggests non-symbiotic hemoglobins affect hormone responses by scavenging NO. Auxin, jasmonic acid, salicylic acid, ethylene and abscisic acid have altered responses when hemoglobins are expressed. Non-symbiotic hemoglobin is a factor during plant development, biotic and abiotic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
125
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 117 publications
0
125
0
Order By: Relevance
“…This led to the suggestion that MPK6 may participate in maintaining poorly translated mRNAs during the stress so that they may be translated upon reoxygenation. Mitochondrial emission of NO also occurs under severe hypoxia (less than 1% oxygen) and was linked to signal transduction and metabolism (Hebelstrup et al, 2012;Hill, 2012). Hebelstrup et al (2012) showed that NO contributes to ethylene-dependent leaf hyponasty.…”
Section: Indirect Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the suggestion that MPK6 may participate in maintaining poorly translated mRNAs during the stress so that they may be translated upon reoxygenation. Mitochondrial emission of NO also occurs under severe hypoxia (less than 1% oxygen) and was linked to signal transduction and metabolism (Hebelstrup et al, 2012;Hill, 2012). Hebelstrup et al (2012) showed that NO contributes to ethylene-dependent leaf hyponasty.…”
Section: Indirect Sensingmentioning
confidence: 99%
“…It has been known for a considerable time that the NO scavenger HB1 contributes to the regulation of low-oxygen gene regulation and metabolism during seed development and transient hypoxia in several species (Hill, 2012). Therefore, low-oxygentriggered NO production and HB1 scavenging may be involved in the regulation of group VII ERF turnover.…”
Section: Direct Oxygen Sensing Regulates the Turnover Of Transcriptiomentioning
confidence: 99%
“…NO is a hormone-like radical that modulates several aspects of the plant physiology, including plant immunity, seed germination, de-etiolation, apoptosis, stomata guard cells opening/closure and the rhizobia-legume symbiosis 111122 . Scavenging of NO is considered a function of plant Hbs 11, 123126 . During this process, oxygenated plant Hbs react with NO producing nitrate and oxidizing ferrous Hb to the ferric form.…”
Section: Postulated Functions For Rice Hemoglobinsmentioning
confidence: 99%
“…This process regenerates ferrous Hb which is able to bind NO in a cyclic pathway referred to as the Hb/NO cycle 126, 134 . The operation of this cycle appears to be involved in maintaining an active metabolism in the plant cells 11 . Rice Hb1 exhibits NO dioxygenase activity (k obs, NOD = 90 s -1 ) 135 thus a possible function of Hbs into the rice physiology is modulating levels of NO by scavenging NO.…”
Section: Postulated Functions For Rice Hemoglobinsmentioning
confidence: 99%
“…17 Oxyhemoglobin reacts very rapidly with NO and regulating cellular NO levels is a more plausible function of these Hbs. 2 The Hb-mediated alterations of cellular NO interfere with hormone signaling as NO acts as a messenger in hormone synthesis and response. There are results of several published studies that could be interpreted in this fashion.…”
mentioning
confidence: 99%